Community Service to Encourage Innovation and Research among Teachers - Mujiati; Nasir; Wijaya Rauf, Budi; Fatmawati, Titi; Yusuf Deluma, Ridwan; Yunarzat, Ersyanda; Ragil Nazar, Erhy; Fadli, Muhammad; Yagri; Rismawati, Besse (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Teachers in North Kolaka Regency face serious challenges in meeting the requirements for scientific publication as a prerequisite for promotion, in accordance with Regulation of the Minister for Administrative and Bureaucratic Reform (Permennegpan and RB) Number 16 of 2009. Most teachers still struggle with limited time, lack of technical training, minimal mentoring, and restricted access to research resources. To address these issues, a community service program was conducted in the form of intensive training and mentoring in scientific writing aimed at enhancing teacher professionalism, encouraging innovation, and accelerating career advancement. The program was held on July 17, 2025, at Hotel Utama Hall, Lasusua, using a blended learning approach that combined face-to-face (offline) sessions with online mentoring via Zoom. Training materials included scientific writing modules, reference management software (Mendeley), Publish or Perish, and the introduction of the Open Journal System (OJS). The methods covered socialization, brainstorming research ideas, writing practice, literature and methodology training, classroom action research (CAR) workshops, and mentoring for publication through OJS. The results indicated a significant improvement in teachers’ skills in writing scientific articles, greater confidence to publish, and better understanding of electronic journal workflows. Identified challenges highlighted time constraints and limited technical skills, but the program provided solutions through continuous mentoring. In conclusion, the training effectively enhanced teachers’ competencies, fostered a culture of research, and supported career promotion. It is recommended that local governments, schools, and universities expand access to sustainable mentoring, both online and offline, to strengthen the culture of scientific publication at the local level.